2016
DOI: 10.1080/00325481.2016.1241129
|View full text |Cite
|
Sign up to set email alerts
|

Lipid effects of switching from prescription EPA+DHA (omega-3-acid ethyl esters) to prescription EPA only (icosapent ethyl) in dyslipidemic patients

Abstract: In this real-world retrospective analysis, switching high-risk statin-treated patients from omega-3-acid ethyl esters to icosapent ethyl resulted in favorable lipid changes. The analysis was limited by the small patient numbers, but lipid results were consistent with randomized controlled trials and previous case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover, EPA lowered TG levels and exhibited anti-inflammatory effects ( 62 ). Statin-treated patients with HTG showed favorable lipid changes upon switching to icosapent ethyl, a highly purified, stable ethyl ester of EPA ( 63 ). The results of the REDUCE-IT study demonstrated that icosapent ethyl decreased TG levels and reduced the risk of the trial’s primary CV endpoint by 25%, although the causal relationship between the two was not proven ( 64 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…Moreover, EPA lowered TG levels and exhibited anti-inflammatory effects ( 62 ). Statin-treated patients with HTG showed favorable lipid changes upon switching to icosapent ethyl, a highly purified, stable ethyl ester of EPA ( 63 ). The results of the REDUCE-IT study demonstrated that icosapent ethyl decreased TG levels and reduced the risk of the trial’s primary CV endpoint by 25%, although the causal relationship between the two was not proven ( 64 ).…”
Section: Residual Risk Factorsmentioning
confidence: 99%
“…In order to control this inflammatory process and the obesity comorbidities, some strategies are used, such as changes in diet, which include the reduction of SFA sources and an increase in the consumption of MUFA and polyunsaturated fatty acids (PUFA), which are associated with cardiovascular protection, acting on atherosclerosis [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various meta-analyses and epidemiological studies have demonstrated the benefit of PUFA, mainly PUFA-n3 (EPA and DHA), as agents for preventing heart failure [ 63 ]. The PUFA-n3 effects have been observed on dyslipidemia [ 64 ], blood pressure disturb via the NO decreased production [ 65 ], haemostasis disorder [ 66 ], and inflammation dysfunction [ 67 ].…”
Section: Discussionmentioning
confidence: 99%